Emerging Issues in Islamic Finance Law and Practice in Malaysia - Oseni, Umar A. (Emerald Publishing Limited, 2019)
Through a thorough analysis of emerging legal and regulatory issues in Islamic finance law and practice in Malaysia, this exciting new study covers issues such as blockchain technology, anti-money laundering, and FinTech in Islamic finance.